Hubungan Konsumsi Ikan Berdasarkan Jenis dan Cara Pengolahannya dengan Kadar Gula Darah Penderita Diabetes Mellitus Tipe II di Wilayah Kerja Puskesmas Poasia - Rahmi, Silvy Aulia; Rizka, Linda Ayu; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Type II DM is rapidly becoming one of the most common non-communicable diseases globally and regionally, in Indonesia almost all provinces showed an increase in prevalence in 2013-2018, except for East Nusa Tenggara, at the Poasia public Health Center there were 101 people with DM. Omega 3 can reduce the risk of diabetes. Consumption of fatty fish may be beneficial to reduce the risk of diabetes. The type of research used in this research is analytic observational, using a cross sectional approach. The study population was patients with type II DM in 2020 as many as 101 people and a sample of 81 using the Slovin formula with purposive sampling sampling technique. The data were obtained using a semi quantitative food frequency questionnaire (SQ FFQ), processed using the Mann-Whitney test. The results of the study showed that there was no relationship between fish processing methods and blood sugar levels when patients with type II DM in the Poasia public Health Center Work Area with a p-Value value. 0.24. there is no relationship between the type of fish and blood sugar levels when patients with type II DM in the Poasia Public Health Center Work Area with a p-value of 0.519 Conclusion that there is no relationship between fish consumption based on the type and way of processing with the blood sugar levels of patients with DM type II in the Working Area of Poasia Public Health Center.